Implementation of monetary and macroprudential policies: a critical review - Lubis, Alexander; Alexiou, Constantinos; Nellis, Joseph G. (Business & Economics Society International, 2017)
The emergence of macroprudential policies by Central Banks, as a means of promoting financial stability, has raised many questions regarding the interaction between them. Given the limited number of studies available, this paper sheds light on this issue by providing a critical and systematic review of the literature. The paper begins with a discussion of the trade-off between price stability and financial stability. We find that financial intermediation acts as the main channel in connecting monetary and macroprudential policies. We find that the theoretical and empirical studies are grouped around four main mechanisms in explaining this interaction: cost of funds, collateral constraint, financial intermediaries and payment systems. By examining these mechanisms, it is argued that monetary policy alone is not sufficient for maintaining macroeconomic and financial stability and macroprudential policies need to supplement monetary policy to achieve price and financial stability. We also find that the role of the exchange rate is critical in the implementation of monetary and macroprudential policies in emerging markets. Volatile capital flows pose another challenge for the implementation of monetary and macroprudential policies. The arrangement of monetary and macroprudential policies also varies across countries, depending on the challenges and institutional arrangements in a particular country. Consequently, a number of implications for theory, policy and practice are proposed.
Keywords: monetary policy; macroprudential policy; capital flows; payment system; systematic